2004
DOI: 10.1177/152692480401400203
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity of Herbal Remedies: An Emerging Dilemma

Abstract: The surge in consumption of herbal remedies has been stimulated by several factors, including the notion that all herbal products are safe and effective, consumers becoming more proactive in self-treating, and lack of regulation by the Food and Drug Administration. Although herbal remedies are generally perceived as harmless, reports of hepatotoxicity associated with herbal use are accumulating, suggesting they are not completely innocuous. On the basis of various case reports, the liver injury from herbal rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…Most reports of toxic effects due to the use of herbal medicines and dietary supplements are associated with hepatotoxicity although reports of other toxic effects including kidney, nervous system, blood, cardiovascular and dermatologic effects, mutagenicity and carcinogenicity have also been reported (Saad et al, 2006;See et al, 2010). Hepatic impairment resulting from the use of conventional drugs is widely acknowledged, but there is less awareness of the potential hepatic toxicity of herbal preparations and other botanicals, many of which are believed to be harmless and are commonly used for self-medication without supervision (Chitturi and Farrell, 2000;Pak et al, 2004;Mohanty et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports of toxic effects due to the use of herbal medicines and dietary supplements are associated with hepatotoxicity although reports of other toxic effects including kidney, nervous system, blood, cardiovascular and dermatologic effects, mutagenicity and carcinogenicity have also been reported (Saad et al, 2006;See et al, 2010). Hepatic impairment resulting from the use of conventional drugs is widely acknowledged, but there is less awareness of the potential hepatic toxicity of herbal preparations and other botanicals, many of which are believed to be harmless and are commonly used for self-medication without supervision (Chitturi and Farrell, 2000;Pak et al, 2004;Mohanty et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There has been suggestions and recommendations on the need to implement increase public awareness and education programs for healthcare professionals about the potential dangers of herbal preparations, in addition to the regulation of their proliferation by the various Food and Drug Administrations (Chitturi and Farrell, 2000;Pak et al, 2004;Joshua et al, 2010). In spite of the high consumption of herbal products or remedies among the Nigerian population and in most developing countries, much attention has not been paid to the evaluation of the safety of these preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a growing concern about the safety of these botanicals as many studies have reported diverse levels of hepatotoxicity or herbs-induced liver injury [3,5,6]. This is because natural products are foreign to the body and need metabolic degradation to be eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, numerous works have been published signaling the potential toxicological effects that these products could also possess (Marcus & Snodgrass, 2005;Pak et al, 2004) Therefore, the investigation of the acute toxicity is the first step in the toxicological analysis of herbal drugs (Lorke, 1983).…”
Section: Discussionmentioning
confidence: 99%